2023
DOI: 10.1029/2022ja031194
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Predictability of the High‐Energy Tail of MEE Precipitation Based on Solar Wind Properties

Abstract: Energetic particle precipitation (EPP) causes chemical changes in the upper atmosphere (≳50 km), for example, by creating NO x and HO x gasses (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 65 publications
(160 reference statements)
2
8
0
Order By: Relevance
“…(2022) suggested that the delay between relativistic electron fluxes and the plasma density n sw (or velocity V sw ) of solar wind is around 10 hr. Moreover, substorm injection and solar wind pressure can also regulate the fluxes of sub‐MeV electrons (Salice et al., 2023; Tyssoy et al., 2021). In this study, we use the time delay between the wave detection and the index measurement to modify the AE and P d indices.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…(2022) suggested that the delay between relativistic electron fluxes and the plasma density n sw (or velocity V sw ) of solar wind is around 10 hr. Moreover, substorm injection and solar wind pressure can also regulate the fluxes of sub‐MeV electrons (Salice et al., 2023; Tyssoy et al., 2021). In this study, we use the time delay between the wave detection and the index measurement to modify the AE and P d indices.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This is consistent with the increased intensification of wave‐particle interactions of both the chorus whistler mode and plasmaspheric hiss in geomagnetic disturbed periods. For >292 keV the maximum precipitating fluxes is delayed a day or two, owing to the time it takes to accelerate the electrons to the respective energies (Nesse Tyssøy et al., 2021; Salice et al., 2023) suggesting that it is partly a product of accelerated seed particles tens of keV electrons. In the following days, both the precipitation from the main radiation belt and the slot region subside.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, by examining a subset of absolute E1 and E3 events with similar/overlapping >43 keV peak fluxes, we seek to gain a deeper understanding of the specific conditions associated with acceleration and precipitation of the high-energy tail. The >292 keV peak flux correlates with the >43 keV peak flux; however, for a specific >43 keV value, the corresponding >292 keV peak flux can vary by an order of magnitude (Salice et al, 2023). Hence, exploring the relative increase between >43 and >292 keV peak fluxes allows for further insight into the conditions favorable for generating a high-energy tail, independent of the initial >43 keV flux level and total energy flux.…”
Section: Methodsmentioning
confidence: 99%
“…The Medium Energy Proton and Electron Detectors (MEPED) aboard the Polar Operational Environmental Satellites (POES) and European Organisation for the Exploitation of Meteorological Satellites (EUMETSAT) MetOp have the advantage of observing within the bounce loss cone (BLC) at polar latitudes, with several operational satellites over multiple solar cycles. Nonetheless, due to instrumental challenges and different data handling within the community, parameterization of MEE leads to a large range of ionization and electron flux estimates (Nesse Tyssøy et al, 2022;Sinnhuber et al, 2022) and is currently a highly active field of research (Beharrell et al, 2015;van de Kamp et al, 2016;van de Kamp et al, 2018;Mironova et al, 2019;Pettit et al, 2019;Tyssøy et al, 2019;Duderstadt et al, 2021;Partamies et al, 2021;Tyssøy et al, 2021;Tyssøy et al, 2021;Babu et al, 2022;Nesse Tyssøy et al, 2022;Zúñiga López et al, 2022;Babu et al, 2023;Nesse et al, 2023;Salice et al, 2023). Other initiatives, such as the UARS satellite (Winningham et al, 1993) and the ELFIN twin CubeSats (Angelopoulos et al, 2023), have also monitored high-energy EEP within the BLC but not with the same coverage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation